The initial draining lymph node primes the bulk of the CD8 T cell response and influences memory T cell trafficking after a systemic viral infection. - Matthew R Olson; Daniel S McDermott; Steven M Varga (PLoS Pathogens)
Lymphocytic choriomeningitis virus (LCMV) causes a systemic infection in mice with virus replication occurring in both peripheral tissues and secondary lymphoid organs. Because of the rapid systemic dissemination of the virus, the secondary lymphoid organs responsible for the induction of the LCMV-specific CD8 T cell response are poorly defined. We show that the mediastinal lymph node (MedLN) serves as the primary draining lymph node following LCMV infection. In addition, we demonstrate that the MedLN is responsible for priming the majority of the virus-specific CD8 T cell response. Following resolution of the acute infection, the draining MedLN exhibits characteristics of a reactive lymph node including an increased presence of germinal center B cells and increased cellularity for up to 60 days post-infection. Furthermore, the reactive MedLN harbors an increased frequency of CD62L(-) effector memory CD8 T cells as compared to the non-draining lymph nodes. The accumulation of LCMV-specific CD62L(-) memory CD8 T cells in the MedLN is independent of residual antigen and is not a unique feature of the MedLN as footpad infection with LCMV leads to a similar increase of virus-specific CD62L(-) effector memory CD8 T cells in the draining popliteal lymph node. Our results indicate that CD62L(-) effector memory CD8 T cells are granted preferential access into the draining lymph nodes for an extended time following resolution of an infection.